New Onset of Diabetes in Adults with Post-Covid Infection in a TertiaryCare Hospital - Karthik Meruva; Alekhya Abburu; Kainat Aftab; Irene Priscilla (International Journal of Medical Research and Review, 2022)
Aim/Scope: This study is aimed to investigate the incidence of diabetes after infection with thecoronavirus (COVID-19). SARS COV2 is a rapidly spreading disease which causes morbidity andmortality. One of the most important complications associated with covid 19 is Diabetes Mellitus. Materials & Methods: This was a retrospective descriptive study of (50 diabetic and 50 non-diabetic) patients who had a previous history of covid-19 and who are infected during the secondwave (Aug’21-Oct’21) at a tertiary care hospital, Hyderabad, India. Data collected including patientdemographic and baseline characteristics like patient’s age, sex and history of covid infection wereanalyzed using Statistical Package for Social Sciences (SPSS) software version 22.0. Results: In thestudy among covid infected(n=50) subjects who were tested diabetic after Long Covid, 28(56%)were hospitalized, 13(26%) were found to have ICU admissions and 9(18%) were discharged withmild covid symptoms and the subjects(n=50) who didn’t have any symptoms of diabetes after LongCovid, majority 32(64%) were found to be discharged with mild covid symptoms, 5(10%) werefound to have ICU admissions and 13 (26%)were found to be hospitalized with the critical covidcondition. It was observed that patients hospitalized with critical covid conditions were susceptible toonset of diabetes (p-value: 0.10) Conclusion: This study showed a high incidence of complicationsin patients infected with COVID-19 with diabetes being the most common one. Patients with poorglycemic control should be routinely monitored and treated appropriately